Facile one-pot synthesis of chitosan-based nanoparticles for pH-responsive enrofloxacin delivery. (December 2021) - Yang, Jun-Lan; Yuan, Hou-Qun; Liu, Bao-Sheng; He, Jia-Xin; Fan, Qing; Deng, Ke; Song, Deping; Bao, Guang-Ming
Abstract: Enrofloxacin is a broad spectrum antibacterial agent with an excellent killing effect against bacteria, commonly infecting the respiratory and intestinal tracts of livestock and poultry. However, its bitter taste and significant irritation to the gastrointestinal tract often lead to a failure of the commonly used current drug delivery system to achieve the desired therapeutic effect due to inefficient release of drugs. In the present study, pH-responsive enrofloxacin nanoparticles (ENR-NPs ) for treating bacterial infections were fabricated through a facile one-pot approach to achieve the amphiphilic functionalization of chitosan (CS) through acid-labile Schiff-base with cinnamaldehyde and drug encapsulation. The structure and morphology of ENR-NPs were characterized by FTIR, X-Ray Diffraction (XRD), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The ENR-NPs were uniform in size and full in shape with an average particle size of 135 nm. The encapsulation rate (76.61%) and drug loading capacity (3.3%) were measured by ultraviolet spectrophotometry. The in vitro experiments elucidated that the release rate of enrofloxacin from ENR-NPs was significantly faster at pH 5.0 than at pH 7.4 due to the cleavage of the acid-sensitive Schiff-base bond. Further, the antimicrobial studies revealed that the inhibitory effects were improved with the increase of acidity of the culture medium. Therefore, ENR-NPs provide a potential application of enrofloxacin for bacterial-response drug delivery. Graphical Abstract: ga1 Highlights: The enrofloxacin delivery nanosystems ENR-NPs were synthesized by one-pot method. The carriers of ENR-NPs were only made up of natural antimicrobial substances chitosan and cinnamaldehyde via Schiff base. ENR-NPs showed a good pH-responsive release and bacteriostasis properties.